Jenis kelainan anal dan karakteristik pada lelaki yang berhubungan seksual dengan lelaki (LSL) yang melakukan pemeriksaan anoskopi di Klinik Bali Medika Periode Agustus 2014-Agustus 2015 - Purnama, Indah; Kartika Sari, Komang Ayu (E-Jurnal Medika Udayana, 2018)
Anoscopy examination performed to detect abnormalities in anal. This study was to determine the type of abnormalities anal, which obtained from the result of the examination anoscopy, characteristics, and risk factors of the MSM in Bali Meidka Clinic who perform anoscopy examination August 2014-August 2015. This study using medical records by taking cross-sectional data, This study using univariate and bivariate analyzes.Of the 178 samples were succefully carried out a search of medical records, obtained by 0,6% diagnosed with anal cyst, 0,6% with herpes/candida, 44,4% with proctitis, and 15,2% with condyloma. Characteristics of the MSM doing examination anoscopy in Bali Medika Clinic with a high proportion have a high school education amounted to 41,1%, 88,2% unmarried, age group 26-37 years old amounted to 48,3%, frequency of visits anoacopy only one time of a year amounted to 68,8%, not infected with HIV amounted to 72,5%, do not use a condom at last sexual intercourse amounted to 44,4%, type of sexual intercourse at last sexual intercourse is receptive amounted to 34,8%, and examination anoscopy <7 days of last sexual intercourse amounte to 39,8%. LSL with proctitis tends to be found in groups with receptive and inserive sexual intercourse. Keywords: MSM, anoscopy, characteristics.